2021
DOI: 10.1002/jbm.a.37267
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating nanocrystalline cellulose into a multifunctional hydrogel for heart valve tissue engineering applications

Abstract: Functional tissue engineered heart valves (TEHV) have been an elusive goal for nearly 30 years. Among the persistent challenges are the requirements for engineered valve leaflets that possess nonlinear elastic tissue biomechanical properties, support quiescent fibroblast phenotype, and resist osteogenic differentiation. Nanocellulose is an attractive tunable biological material that has not been employed to this application.In this study, we fabricated a series of photocrosslinkable composite hydrogels mNCC-Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…Thanks to its nanofibrillar network, BC can connect with a variety of polymers to form nanocomposites that possess desirable characteristics and processable qualities pertaining to the demands of cardiovascular TE [ 160 ]. Ma et al [ 164 ] fabricated a chain of photocrosslinkable composite hydrogels mNCC-MeGel (mNG) by conjugating TEMPO-modified nanocrystalline cellulose (mNCC) onto the backbone of methacrylated gelatin (MeGel). The mNCC-MeGel (mNG) nanocomposite displayed enhanced mechanical properties.…”
Section: Application Of Blends and Composites Of Bc In Tissue Enginee...mentioning
confidence: 99%
“…Thanks to its nanofibrillar network, BC can connect with a variety of polymers to form nanocomposites that possess desirable characteristics and processable qualities pertaining to the demands of cardiovascular TE [ 160 ]. Ma et al [ 164 ] fabricated a chain of photocrosslinkable composite hydrogels mNCC-MeGel (mNG) by conjugating TEMPO-modified nanocrystalline cellulose (mNCC) onto the backbone of methacrylated gelatin (MeGel). The mNCC-MeGel (mNG) nanocomposite displayed enhanced mechanical properties.…”
Section: Application Of Blends and Composites Of Bc In Tissue Enginee...mentioning
confidence: 99%
“…Therefore, this study demonstrated the efficiency of synthesized composite hydrogels for engineered multilayer heart valve engineering. [ 77 ]…”
Section: Electroactive (Intrinsically Conducting Polymers)‐based Hydr...mentioning
confidence: 99%
“…Therefore, this study demonstrated the efficiency of synthesized composite hydrogels for engineered multilayer heart valve engineering. [77] In another study, Hinderer et al created an electrospinning scaffold consisting of PLA and PEGdma that was compatible with the structure and mechanical properties of the native valve matrix. They introduced important structural valves of the heart valve (collagen type I and Versicane) to the scaffold.…”
Section: Ma Et Al Prepared a New Nanocomposite Hydrogel By Con-mentioning
confidence: 99%
“…232 Interestingly, photocrosslinkable hydrogels constructed using GelMA and nanocellulose have exhibited non-linear biomechanics, suppressed osteo-induction, and improved quiescent fibroblast phenotype for the engineering of heart valves. 233…”
Section: Heartmentioning
confidence: 99%